Letters of Indonesian nationalist Sjahrir to his beloved Maria Duchâteau; A transcultural case of travel writing - Snoek, Kees (Wacana, Journal of the Humanities of Indonesia, 2024)
The letters Indonesian nationalist Sjahrir wrote between 1932 and 1940 to his Dutch beloved Maria Duchâteau illustrate a transcultural case of travel writing. They also illustrate how much he was convinced that Western ideas and attitudes could assist Indonesian people to develop and gain sufficient self-confidence to shake off the colonial yoke. Born into an elite Minangkabau family, Sjahrir studied in Java and The Netherlands, before taking up campaigning for a non-cooperative political party which emphasized the importance of education. This article discusses the period between early 1932 and 26 February 1934, before Sjahrir’s arrest and following imprisonment and exile. In this period of relative freedom (but without Maria, who on 14 May 1932 had been extradited to Holland), Sjahrir travelled a lot throughout Java. In his letters, he gives examples of social injustice and colonial abuse, of the contrast between the beauties of nature and the poverty-stricken inhabitants of Java, and of differences along the lines of ethnicity, social class, and gender.